Students’ participation on speaking online class (a case study) - Inti - Englishtina; Novita - Al Ihyak; Steffie Mega Mahardhika (ETERNAL (English Teaching Journal), 2021)
This paper aims to reveal factors that affect the students' participation in a speaking online class. The subjects are the second and fourth semester students of English department, Language and Culture Faculty, UNTAG Semarang. The research was held during the even semester of the academic year 2020/2021. The research method used in this study is a qualitative method. The data was based on the interview and the questionnaires filled by the students. Some technical issues came up in the online class such as internet connection which mostly became the hottest issue and also the device being used which was sometimes not compatible to the program used in the teaching and learning process. Those issues somehow have affected the online teaching and learning process. The other issues affected in online learning are students’ contribution and students’ condition. For those, it is hoped that the research will give a clearer explanation especially for the teachers who are struggling on teaching the online class and face a similar situation. Therefore, they can cope and handle it better. Keywords: online learning, participation, speaking class